FORMULATION, AND CHARACTERIZATION OF NANOSTRUCTURED LIPID CARRIER (NLC) CONTAINING QUERCETIN - Asti Rahayu; Astrid Kusuma Putri; Nadya Ambarwati; Fithri Farchah Frischah Sari; Rizky Anugrah Dirgantara Putra (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Quercetin, like triterpenoids, decreases blood glucose levels. Quercetin has several limitations including low solubility, low percutaneous permeability, and low bioavailability. The formulation of quercetin preparations in a Nanostructured Lipid Carrier (NLC) system is one solution to increase its solubility. The quercetin NLC system was successfully formulated by the high shear homogenization method at a speed of 6000 rpm. The solid lipid glyceryl monostearate and  sunflower oil play important roles in the formation of NLC. The physicochemical characteristics examined in this study included the particle size, dispersion, viscosity, pH, and entrapment efficiency. The particle size of NLC quercetin ranges from 22.98 ± 0.008 nm to 41.04 ± 0.082 nm, with p-values < 0.05. The dispersion power of quercetin NLC ranges from 5.12 ± 0.11 cm to 7.01 ± 0.28 cm, p values < 0.05. The resulting pH range is 7.3 ± 0.01 to 7.4 ± 0.01, and the resulting viscosity is 223.7 ± 9.8 cps to 492.0 ± 0.0 cps. Entrapment efficiency range of (62.20 ± 0.245)% to (86.17 ± 0.287)% ( p < 0.05). The ratio of solid lipid concentration to liquid lipid concentration in NLC quercetin has a significant effect on particle size, dispersion, and entrapment efficiency.  Keywords: Nanostructured Lipid Carrier, Quercetin, Lipid, Glyceryl Monosterate, Sunflower Oil